Pemanfaatan Modal Sosial Petani Ikan Pasca Tubo Balerang dalam Mendapatkan Pekerjaan Baru - Ifdal Gusman (Jurnal Sosiologi Andalas, 2019)
Fish farming is the main livelihood of some people around Lake Maninjau. But the thing thatfarmers fear the most is when a disaster called Tubo Balerang comes. This article aims to describe the types oflivelihoods of fish farmers post-Tubo Balerang and explain the workings of social capital to survive fish farmersin the aftermath of Tubo Balerang. The approach used in this study is a qualitative approach to the type ofdescriptive research with in-depth interview and observation data collection techniques. From the results it wasfound that fish farmers survived by finding another job until things returned to stability. The work is like: (1)Daily merchants. (2) Breeding quails. (3) Work as a driver. (4) Selling fish medicine. (5) Rice milling workers.While social capital is utilized to survive, namely: (1) Trust, namely the existence of a long-standingcooperative relationship, ties of kinship, mutually beneficial business, and feelings of mutual need. (2) Networkamong fellow fish farmers, network of fish farmers with local investors, and networks with their relatives. (3)Norms, namely the fulfillment of rights and obligations, and all forms of rules governed in the initialagreement